Sociological Exploration of Intentions in Marriage: A Study of the Living Hadith of the Prophet Muhammad - Zuhdi, Muhammad (al-Rasῑkh: Jurnal Hukum Islam, 2025)
The rising divorce rate in Indonesia reflects a shift in the meaning and orientation of marriage. Many couples enter marriage not out of sincere spiritual intent or devotion but are driven by materialistic and social motivations that are temporary in nature. This study aims to explore the concept of intention (niyyah) in marriage based on the teachings of Prophet Muhammad (peace be upon him) and its sociological implications for marital stability in contemporary society. The research employs a qualitative, descriptive–exploratory approach through the study of relevant hadiths and in-depth interviews with Muslim couples and religious counselors. The findings indicate that intention plays a significant role in determining the quality and sustainability of marriage. Couples who marry with sincere and worship-oriented intentions tend to demonstrate healthier communication, stronger commitment, and greater resilience in facing life’s challenges. Conversely, marriages founded on worldly motives such as wealth, social status, or physical attraction are more vulnerable to conflict, disappointment, and divorce. These findings align with the Prophet’s warning that impure intentions lead to humiliation and failure within marriage. The study concludes that purifying one’s intention is a fundamental step toward building a harmonious family amid the challenges of modern materialism and individualism. Practically, the results underscore the importance of incorporating spiritual and ethical values into premarital education for Muslim families.